PENGARUH PEMBELAJARAN BERDIFERENSIASI TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPAS DI KELAS IV SD SWASTA BUDI MULIA BINJOHARA TAHUN PEMBELAJARAN 2023/2024 - Iskawati Maria Tumanggor; Antonius Remigius Abi; Bogor Lumbanraja; Dyan Wulan Sari HS; Ester Julinda Simarmata (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research aims to determine the effect of using Differentiated Learning on student learning outcomes in Topic B: Photosynthesis, the Most Important Process on Earth in class IV of Budi Mulia Binjohara Private Elementary School for the 2023/2024 academic year. In this research, quantitative research methods and pre-experimental research were used. The population of this research was the entire fourth grade of Budi Mulia Binjohara Private Elementary School, totaling 22 students. Sampling was taken using saturated sampling and the sample used was class IV, totaling 22 students. To determine students' initial abilities, this researcher conducted a PreTest with an average score of 59.09 which was in the category of not meeting the learning objectives. Then the results of the PostTest have increased from the PreTest results given previously with the average student score reaching 82 in the good category. The level of success in student learning outcomes has increased as evidenced by the results of the correlation test calculation which was obtained at 0.661, which means r count (0.661) > r table (432). Next is hypothesis testing (t-test) where t count ≥ t table, namely 3.940 ≥ 2.060 so that it can be stated that Ha is accepted and Ho is rejected. This shows that there is a significant positive influence from the use of differentiated learning on student learning outcomes on topic B Photosynthesis, the Most Important Process on Earth in class IV of Budi Mulia Binjohara Private Elementary School for the 2023/2024 Academic Year.